Pengukuran Dan Pengendalian Debu Di Sentra Pengrajin Gitar Sukoharjo - Farhana Syahrotun Nisa (IJECS: Indonesian Journal of Empowerment and Community Services, 2022)
Sukoharjo guitar craftsman who are exposed to continuous dust and do not use proper breathing apparatus when making guitars are at risk of respiratory distress because the dust content on the job site has never been measured and   has not been controlled in order to reach the safe limit. The target of this activity is the guitar craftsman in Mancasan Village, Baki Subdistrict, Sukoharjo. The target in the implementation of this activity is to improve the knowledge and skills of workers about the dangers and impacts of exposure to wood dust in the workplace, while for its external in the form of national scientific journals, videos, and print or online media. The method of implementation of devotion using the method of measuring the dust content of the work environment and health counseling methods with the media, including: dust measuring instruments, questionnaires, power points, videos, and other media. As a result of community service activities it was concluded that the total dust content at 5 Sukoharjo guitar craftsman locations exceeded NAB and all craftsman experienced respiratory problems. Therefore, it is necessary to take measurement and dust control in order for the guitar craftsman to work safely and safely.